(untitled) (Filološke pripombe, 2019)
Synonymous possessive statements with different predicates are examined on the basis of Novgorodskaya chronicle. The specific features of the grammatical meaning of modes of possessor’s expression are investigated in sentences with the verb «быти». It has been revealed, that the choice of the linguistic mode of the subject of a possessive situation depends on a chronicler’s intentions.